Collaborative Governance dalam Pengembangan Agrowisata di Kota Palembang: Studi Kasus Agrowisata Edukasi Sungai Jawi Kecamatan Kalidoni Kota Palembang - Rahmawati, Rahmawati; Marsalina, Rizki (Indonesian Association for Public Administration (IAPA), 2024)
The purpose of this research is to determine and analyze the Collaborative Governance Process in Agrotourism Development in Palembang City (Case Study of Sungai Jawi Educational Agrotourism, Sungai Selincah Village, Kalidoni District in Palembang City). The research method used in this research is a qualitative research method. According to Dermadi (2013:153), the research method is a scientific method for obtaining data with several useful purposes. The scientific method refers to research activities that are based on scientific principles, namely rational, experimental, and systematic. Based on the explanation above, it can be concluded that the research method is a scientific method for obtaining data with certain purposes and applications. Based on the results of research regarding the Collaborative Governance Development Process in Palembang City (case study of Sungai Jawi Educational Agrotourism, Kalidoni District), the Collaborative Governance Process in the development of Jawi River Educational Agrotourism has been carried out through the stages of face to face dialogue, trust building. trust), commitment to the process (commitment to the process), and intermediate outcomes (intermediate results achieved) which have been implemented well.